Power Trading Blockchain using Hyperledger Fabric - Kim, Yonghyun; Kim, Ki Hyung; Kim, Jai Hoon (International Conference on Information Networking, 2020)
Various technologies are mentioned in the 4th Industrial Revolution. One of the emerging issues in the power market is the blockchain-based smart grid network. We propose the architecture of the network by incorporating blockchain technology into the existing smart grid system. The Ethereum and Hyperledger Fabrics are widely used in the blockchain technology as public blockchains and private blockchains, respectively. We describe the network architecture in the smart grid blockchain and compare the performance of transactions processing. The performance analysis shows that Hyperledger Fabric is viable approach by providing pipelined concurrent transaction among peers processing and MVCC(multi-version concurrency control).
Keywords: Concurrent transactions; Industrial revolutions; Performance analysis; Power trading; Smart grid; Smart grid networks; Transaction performance; Various technologies; Ethereum; Hyperledger Fabric; Power trading; Smart grid; Transaction performance